To SIB or not to SIB? A comparative analysis of the commissioning processes of two proposed health-focused Social Impact Bond financed interventions in England. Issue 1 (2nd January 2021) - Fraser, Alec; Tan, Stefanie; Mays, Nicholas
ABSTRACT: We explore the development of two proposed Social Impact Bond (SIB) financed interventions in the UK. This is important because little is known about the processes involved in the localised development of these nascent financing mechanisms. We apply a "decentred" approach to network governance to the case studies – one in which a SIB financed intervention was initiated and another in which it was not. Moving from the prevailing competitive quasi-market commissioning traditions to new forms of integrated commissioning requires a more collaborative approach to service procurement than has typically been the case thus posing dilemmas for the relevant networks.